2016
DOI: 10.1063/1.4971999
|View full text |Cite
|
Sign up to set email alerts
|

Localized holes and delocalized electrons in photoexcited inorganic perovskites: Watching each atomic actor by picosecond X-ray absorption spectroscopy

Abstract: We report on an element-selective study of the fate of charge carriers in photoexcited inorganic CsPbBr3 and CsPb(ClBr)3 perovskite nanocrystals in toluene solutions using time-resolved X-ray absorption spectroscopy with 80 ps time resolution. Probing the Br K-edge, the Pb L3-edge, and the Cs L2-edge, we find that holes in the valence band are localized at Br atoms, forming small polarons, while electrons appear as delocalized in the conduction band. No signature of either electronic or structural changes is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
93
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 72 publications
(110 citation statements)
references
References 82 publications
(169 reference statements)
8
93
0
Order By: Relevance
“…Therefore, an X-ray absorption spectrum should be able to detect both localized charges (typically as small polarons at regular sites or at defects) and delocalized ones, as recently demonstrated in the case of perovskites. 274 It seems however that in the case of TiO2 (Figure 18), the signal is dominated by charge localization, which we found to occur on an ultrafast time scale of < 200 fs (Figure 18d). 272 Recently, time-resolved photoemission has been implemented to probe the interfacial dynamics in transition metal oxides.…”
mentioning
confidence: 71%
“…Therefore, an X-ray absorption spectrum should be able to detect both localized charges (typically as small polarons at regular sites or at defects) and delocalized ones, as recently demonstrated in the case of perovskites. 274 It seems however that in the case of TiO2 (Figure 18), the signal is dominated by charge localization, which we found to occur on an ultrafast time scale of < 200 fs (Figure 18d). 272 Recently, time-resolved photoemission has been implemented to probe the interfacial dynamics in transition metal oxides.…”
mentioning
confidence: 71%
“…In a very recent work, Hill and co-workers reported the first fs magnetic RIXS after photo-doping the Mott insulator Sr 2 IrO 4 , and directly determined its magnetization dynamics 41 . Although concerning solid materials, such studies are also of interest to photovoltaics and photocatalysis when it comes to transition metal oxides 125,156 and perovskites, 157 as the bulk properties of these materials need to be nailed down, which means studying single crystals as was recently demonstrated in the case of TiO 2 158 …”
Section: Applications In Chemistrymentioning
confidence: 99%
“…This difference has been observed experimentally in CH 3 NH 3 PbBr 3 , in which transient hard x-ray spectroscopy showed that photoexcited electrons are delocalized between several Pb atoms but holes were likely localized on a single Br. 39 A range of computational work supports this difference in delocalization, predicting the electron polaron to be larger than the hole polaron. 35,37 The difference in size can be connected to the onset of the hot phonon bottleneck, which has been proposed to stem from spatial overlap of polarons above a critical carrier density.…”
Section: Discussionmentioning
confidence: 91%